2021
DOI: 10.32942/osf.io/t82cf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sea ice and substratum shape extensive kelp forests in the Canadian Arctic

Abstract: The coastal zone of the Canadian Arctic represents 10% of the world’s coastline and is one of the most rapidly changing marine regions on the planet. To predict the consequences of these environmental changes, a better understanding of how environmental gradients shape coastal habitat structure in this area is required. We quantified the abundance and diversity of canopy forming seaweeds throughout the nearshore zone (5 - 15 m) of the Eastern Canadian Arctic using diving surveys and benthic collections at 55 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…This is in agreement with other studies showing that temperature is one of the main predictors that contribute significantly to explaining kelp distribution (Assis et al, 2016;Jayathilake and Costello, 2020;Krause-Jensen et al, 2020). Kelps are sensitive to warming temperatures, which can often be a stressor at warm range edges along temperate coasts (Duarte et al, 2018;Wernberg et al, 2018;Filbee-Dexter et al, 2021), and we have shown that, in our study, L. solidungula was the species with the greatest sensitivity to higher temperatures (which translates later into the species having the highest predicted loss in area). However, many kelp species in the Arctic experience temperatures close to their lower thermal limit and demonstrate improved recruitment and growth under 1-3 • C increases (Filbee-Dexter et al, 2019).…”
Section: Variablessupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with other studies showing that temperature is one of the main predictors that contribute significantly to explaining kelp distribution (Assis et al, 2016;Jayathilake and Costello, 2020;Krause-Jensen et al, 2020). Kelps are sensitive to warming temperatures, which can often be a stressor at warm range edges along temperate coasts (Duarte et al, 2018;Wernberg et al, 2018;Filbee-Dexter et al, 2021), and we have shown that, in our study, L. solidungula was the species with the greatest sensitivity to higher temperatures (which translates later into the species having the highest predicted loss in area). However, many kelp species in the Arctic experience temperatures close to their lower thermal limit and demonstrate improved recruitment and growth under 1-3 • C increases (Filbee-Dexter et al, 2019).…”
Section: Variablessupporting
confidence: 93%
“…Previous and recent research campaigns across the Eastern Canadian Arctic (Filbee-Dexter et al, 2021) collected kelp cover data that allow habitat suitability and percent cover of kelp species to be modeled and predicted throughout this region. Abundance of kelp can be measured in several ways, with biomass per area, number of individuals per area (i.e., density) and percent cover being the three most common.…”
Section: Kelp Covermentioning
confidence: 99%
“…The importance of sea‐ice in modelling Arctic kelp distributions is also reported by Goldsmit et al (2021). It can be expected, however, that contemporary marine forests at the highest latitudes are extremely patchy, persisting only where the ebb and flow of sea ice dynamics facilitate a brief growing season, and frequently occurring at low per area biomasses, depth ranges, and cover compared to marine forests at lower latitudes (Filbee‐Dexter et al, In press; Krause‐Jensen et al, 2012). Diminutive, poorly studied, and potentially more resilient alternate life‐history stages (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, our decision to mask the environmental layers for depositional versus erosional shorelines may have underestimated the amount of Arctic habitat available to marine forests. The northern shorelines of Alaska, which were mostly excluded from our models, are known to host patches of marine forests interspersed among sediment‐laden bays (Wilce & Dunton, 2014), and substrate requirements may be less strict in some species (i.e., Lee (1973) reports on seemingly healthy unattached communities in calm bays, whilst Filbee‐Dexter et al (In press) show that kelp forests in the East Canadian Arctic are also present in sedimentary habitats).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation